Philippines 2000 : a vision for the nation. (Makati City, Philippines : Studio 5 Designs, 1996)
Let it also be made eminently clear that one of the objectives of PHILIPPINES 2000! is to improve the economic landscape in order to create ample opportunity for all who are willing and able to work.
CHAPTER 1. The Filipino People -- 2. Cultural transformation -- 3. A vision for the nation -- 4. Economic Take-off -- 5. Civic Responsibility -- 6. Population -- 7. National Security -- 8. Environment -- 9. International relations.
Keywords: ECONOMIC HISTORY